Role of nutritional status and physical activity in the relationship between sleep quality and cardiometabolic proﬁle of children - Camila Felin Fochesatto (Brazilian Association of Sleep and Latin American Federation of Sleep Societies, 2021)
Objective: To verify if there is an association between sleep quality and cardiometabolic risk factors (CMRF) score of children and the role of nutritional status and physical activity (PA) levels in this relationship. Material and Methods: ross- sectional study, with 83 schoolchildren, aged 6 and 11 years, from Porto Alegre, Brazil. PA was assessed with accelerometer and nutritional status through body mass index. Total cholesterol, triglycerides, glucose, and insulin were collected to calculate CMRF score. Parents’ perception of their children’s sleep was evaluated through a question. Generalized linear models were used. Results: Poor sleep quality was positively associated with CMRF (ß=0.48; CI 95%=0.23;0.73) in relation to those with good sleep quality. A positive association was found in overweight children with poor sleep quality (ß=0.52; CI 95%=0.17;0.86), as well as in inactive children with poor sleep quality (ß=0.58; CI 95%=0.14;1.02) with CMRF. Conclusion: Poor sleep quality integrated with overweight and physical inactivity influences on CMRF of children.